이산화염소에 의한 용존성 망간 산화생성물의 여과막에 의한 제거 - 정지훈; 이석헌 (한국물환경학회, 2002)
Removal of dissolved manganese by chlorine dioxide and membrane filtration was investigated. Dissolved manganese was oxidized rapidly into manganese dioxide particles by chlorine dioxide. The oxidized form was very stable for hours that gravitational separation is not feasible. The particle size distribution(PSD) was analyzed during settlement test. No noticeable chage in PSD was observed. MF filter was not effective to reject the colloidal particles of manganese dioxide formed by chlorine dioxide. However, polysulfone ultrafilter of 50K MWCO showed complete rejection of the colloidal manganese dioxide particles. Adsorption of dissolved manganese on pre-oxidized manganese dioxide particle was 6 - 7 mmole Mn(II) per mole MnO2(s). Enhanced removal by continuous oxidation and MF filtration was suggested by batch experiments.